Kinerja Layanan Helpdesk Mendukung Peminjaman Melalui Aplikasi Booking Book di Era New Normal: Studi Kasus Pada UPT Perpustakaan Universitas Syiah Kuala - Zakiah; Faizah (Jurnal IPI (Ikatan Pustakawan Indonesia), 2021)
Writing this paper aims to determine how the role of the help desk in supporting services in the new normal era. The USK library's UPT help desk is provided through two models, namely manual-based and on-line. In this study the authors only focused on the performance of the helpdesk services manually in managing and serving the borrowing process that must be done through the booking book application first. Data collection techniques are carried out through observation, interviews, and documentation. The results of the research will be displayed in table form by calculating the number of bookers and the number of collections borrowed. The new normal era USK library UPT help desk manual is assigned to handle especially requests for book collections for borrowing through the booking book application. This research proves that the role of the help desk is very necessary, especially in the new normal era because visitors are not allowed to enter freely and in a crowd.